Biochemical Marker Assessment of Chronic Carbamazepine Exposure at Environmentally Relevant Concentrations in Juvenile Common Carp (Cyprinus carpio) - Xinyue Liang; Zsolt Csenki; Bence Ivánovics; Illés Bock; Balázs Csorbai; József Molnár; Erna Vásárhelyi; Jeffrey Griffitts; Árpád Ferincz; Béla Urbányi; András Ács (MDPI AG, 2022)
Worldwide, the anticonvulsant drug carbamazepine (CBZ) is the most frequently identified pharmaceutical residue detected in rivers. Reported chronic effects of CBZ in non-target freshwater organisms, particularly fish, include oxidative stress and damage to liver tissues. Studies on CBZ effects in fish are mostly limited to zebrafish and rainbow trout studies. Furthermore, there are only a few chronic CBZ studies using near environmental concentrations. In this study, we provide data on subacute effects of CBZ exposure (28 days) to common carp (Cyprinus carpio), employing a set of biochemical markers of damage and exposure. CBZ was found to induce a significant change in the hepatic antioxidant status of fish subjected to 5 µg/L. Moreover, with increasing concentrations, enzymatic and non-enzymatic biomarkers of oxidative defence (catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR), DNA strand breaks)), toxicant biotransformation (ethoxyresorufin-o-demethylase (EROD), glutathione-S-transferase (GST)), and organ and tissue damage (lactate dehydrogenase (LDH), cetylcholinesterase (AChE)) were altered. The AChE, LDH, and lipid peroxidation (LPO) results indicate the occurrence of apoptotic process activation and tissue damage after 28 days of exposure to CBZ. These findings suggest significant adverse effects of CBZ exposure to common carp at concentrations often found in surface waters.